Acceptability, Usability, and Performance of Lateral Flow Immunoassay Tests for Severe Acute Respiratory Syndrome Coronavirus 2 Antibodies: REACT-2 Study of Self-Testing in Nonhealthcare Key Workers. (4th October 2021) - Davies, Bethan; Araghi, Marzieh; Moshe, Maya; Gao, He; Bennet, Kimberly; Jenkins, Jordan; Atchison, Christina; Darzi, Ara; Ashby, Deborah; Riley, Steven; Barclay, Wendy; Elliott, Paul; et al.
Abstract: Background: Seroprevalence studies are essential to understand the epidemiology of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Various technologies, including laboratory assays and point-of-care self-tests, are available for antibody testing. The interpretation of seroprevalence studies requires comparative data on the performance of antibody tests. Methods: In June 2020, current and former members of the United Kingdom police forces and fire service performed a self-test lateral flow immunoassay (LFIA), had a nurse-performed LFIA, and provided a venous blood sample for enzyme-linked immunosorbent assay (ELISA). We present the prevalence of antibodies to SARS-CoV-2 and the acceptability and usability of self-test LFIAs, and we determine the sensitivity and specificity of LFIAs compared with laboratory ELISA. Results: In this cohort of 5189 current and former members of the police service and 263 members of the fire service, 7.4% (396 of 5348; 95% confidence interval [CI], 6.7–8.1) were antibody positive. Seroprevalence was 8.9% (95% CI, 6.9–11.4) in those under 40 years, 11.5% (95% CI, 8.8–15.0) in those of nonwhite ethnicity, and 7.8% (95% CI, 7.1–8.7) in those currently working. Self-test LFIA had an acceptability of 97.7% and a usability of 90.0%. There was substantial agreement between within-participant LFIA results (kappa 0.80; 95% CI, 0.77–0.83). The LFIAs had a similar performance: compared with ELISA, sensitivity was 82.1% (95% CI, 77.7–86.0) self-test and 76.4% (95% CI, 71.9–80.5) nurse-performed with specificity of 97.8% (95% CI, 97.3–98.2) and 98.5% (95% CI, 98.1–98.8), respectively. Conclusions: A greater proportion of this nonhealthcare key worker cohort showed evidence of previous infection with SARS-CoV-2 than the general population at 6.0% (95% CI, 5.8–6.1) after the first wave in England. The high acceptability and usability reported by participants and similar performance of self-test and nurse-performed LFIAs indicate that the self-test LFIA is fit for purpose for home testing in occupational and community prevalence studies. Abstract : Self-test lateral flow immunoassays (LFIAs) had a high acceptability and usability and similar performance to nurse-performed LFIAs. Self-test LFIAs are suitable for home-testing in SARS-CoV-2 prevalence studies in nonhealthcare worker populations.